Pathway analysis of the effect of virgin coconut oil on suppressing colonic mucosal inflammation and clinical symptoms in ulcerative colitis - Ni Made Rika Trismayanti; Kusworini Handono; Dian Handayani; Umi Kalsum; Ettie Rukmigarsari (Pensoft Publishers, 2024)
Ulcerative colitis (UC) is an inflammatory disease of the large intestine characterized by ulceration and diffuse mucosal damage. Virgin coconut oil (VCO), with its anti-inflammatory properties, emerges as a potential preventive solution for UC. VCO can be an alternative because it has relatively few side effects compared to chemical drugs. This study aims to determine the effect of VCO on suppressing colonic mucosal inflammation and clinical symptoms of UC through pathway analysis. A model grounded in equations within path analysis emerges as a superior framework compared to regression for elucidating the collective impact of PPAR-γ expression, NF-κB p65 expression, the quantity of M1 and M2 macrophages, the M1/M2 macrophage ratio, as well as TNF-α, IL-6, and IL-10 levels, and the MCHI score on DAI in UC model mice. Achieving an R2y9 value of 0.998 vastly surpasses the R2 value of 0.252 attained through regression analysis. This R2y9 value denotes that the cumulative influence of the mentioned variables on DAI stands at an impressive 99.8%. Drawing from the outcomes of pathway analysis, it is evident that VCO exhibits anti-inflammatory properties in UC model mice. To advance this understanding, future investigations could focus on refining VCO into a medicinal formulation suitable for commercial consumption.